The Impact of Marketing Information System Components on Organizational Decision Making: A Case of Jordanian Five Star Hotels - Shkeer, Amged Saleh; Awang, Zainudin (International Review of Management and Marketing, 2019)
An accurate decision is vital for an organization to survive in highly competitive marketplaces. The most critical factor contributing to the accuracy of decision making is the Management Information System (MIS). This study intended to determine the impact of MIS on decision making process among managers in Five Star Hotels in Jordan. The study employed simple random sampling method to select 300 respondents from the sampling frame which consists of managers and decision makers of the hotels. The study sent out the self-administered questionnaires to the selected respondents to respond at their own convenient time. After a few weeks, a total of 230 responses were received and usable for analysis. The study employed the second generation method of analysis namely Structural Equation Modelling (SEM) procedure in IBM-SPSS-AMOS 25.0 to model and test the hypotheses. The results showed MIS, which consists of Marketing Research, Marketing Record, Marketing Intelligence and Decision Support System has significant impact on Decision Making Process. More importantly, it contributed about 97% of the Decision Making Process in the five star hotels in Jordan. The testing of hypotheses for the MIS components found all components, except Marketing Research, has significant influence on Management Decision Making among Five Star Hotels in Jordan. Keywords: Decision making process, Marketing Information System, components, five-star hotels. JEL Classifications: M1, M31, M300 DOI: https://doi.org/10.32479/irmm.8873